PENGARUH LEVERAGE, PROFITABILITAS, BEBAN PAJAK TANGGUHAN DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Teguh Erawati; Yung Siang (Universitas Muhammadiyah Makassar, 2021)
This study aims to examine the effect of leverage, profitability, deferred tax expense, and tax planning on earnings management. The population used in this study is manufacturing in the basic and chemical industrial sectors which have been listed on the Indonesia Stock Exchange (IDX) in 2014-2019. The sample used is manufacturing companies in the basic industrial sector and chemical industry, using purposive sampling method. With this purposive sampling method, a sample of 15 companies was obtained with 90 annual reports. The type of data used is secondary data obtained from www.idx.co.id. This study uses Multiple Linear Regression Analysis. Data analysis techniques in this study are descriptive statistics, classical assumption test and multiple linear regression test. The software used is SPSS 23. The test results of this study use multiple linear regression analysis. The results showed that leverage, profitability, and tax planning had a positive effect on earnings management, while deferred tax expense had no effect on earnings management.